PERANCANGAN VIDEO PROFILE SEBAGAI MEDIA PROMOSI DAN INFORMASI DI SMK AVICENA RAJEG TANGERANG - Wahyu Hidayat; Anita B. Wandanaya; Recha Fadriansyah (UNIVERSITAS RAHARJA, 2016)
Technological development especially in the field of information and communications has grown in such a rapidly especially in the field of multimedia. This is according to an institution to develop information from various media in accordance with the development. A wide variety of media promotion and the information is urgently needed, for it required media interactive and efficient promotion in order to attract students and new students. one of the interactive and efficient media are audio visual media. SMK Avicena Rajeg Tangerang is the agency or educational institution that is always in order to improve the quality of education bersain in the current era of globalization, but the school has not had media full and effective information about the school profile at once can be a means of promotion to the public. Then a study with the title